Perspectives in business informatics research : 16th International Conference, BIR 2017, Copenhagen, Denmark, August 28-30, 2017, Proceedings - Johansson, Björn; Møller, Charles; Chaudhuri, Atanu; Sudzina, Frantisek (Springer, 2017)
This book constitutes the proceedings of the 16th International Conference on Perspectives in Business Informatics Research, BIR 2017, held in Copenhagen, Denmark, in August 2017. This year the BIR conference attracted 59 submissions from 23 countries. They were reviewed by 45 members of the Program Committee, and as a result, 17 full papers and 3 short papers were selected for presentation at the conference and publication in this volume. They are organized in sections on enterprise architecture, business process management, business analytics, information systems applications, and information systems development. In addition, the summaries of the two conference keynotes are also included. This year, the conference theme was the digital transformation, which will impact most businesses, organizations and societies and call for new and radical approaches to how we adopt, use and manage IT.
Keywords: Business -- Data processing -- Congresses.; Management information systems -- Congresses.; elektronické knihy; electronic books